Sustaining efficient production of aqueous iron during repeated operation of Fe(0)-electrocoagulation. (15th May 2019) - Müller, Simon; Behrends, Thilo; van Genuchten, Case M.
Abstract: Iron-electrocoagulation is a promising contaminant (e.g. arsenic) removal technology that is based on electrochemical Fe(II) production from steel electrodes and subsequent transport of Fe(II) to the bulk solution, where contaminant removal occurs. Although Fe-electrocoagulation systems have been shown to effectively remove contaminants in extended field trials, the efficiency of field systems can be lower than in laboratory studies. One hypothesis for this disparity is that the Faradaic efficiency of short-term laboratory experiments is higher than field systems operated over extended periods. The Faradaic efficiency is a pivotal performance indicator that we define as the measured Fe dosage normalized by the theoretical Fe dosage calculated by Faraday's law. In this work, we investigated the Faradaic efficiency in laboratory experiments for up to 35 operating cycles (>2 months) with varied Fe(0) anode purity, charge dosage rate, and electrolyte composition. Our results showed that the Faradaic efficiency decreased continuously during repeated operation under typical field conditions (charge dosage rate = 4 C/L/min, synthetic groundwater) regardless of the Fe(0) anode purity, leading to a Faradaic efficiency ≈ 0.6 after 2 months. By contrast, increasing the charge dosage rate to ≥15 C/L/min produced a Faradaic efficiency >0.85 over the entire experiment for both Fe(0) anode purities. Electrolyte solutions free of oxyanions also resulted in sustained Faradaic efficiency >0.85, regardless of the charge dosage rate. Our results confirm a previously proposed relationship between low Faradaic efficiency and the formation of macroscopic electrode surface layers, which consist of Fe (oxyhydr)oxides on the anode and a mixture of Fe (oxyhydr)oxides and calcite on the cathode. Based on these results, we discuss potential strategies to maintain a high Faradaic efficiency during Fe-electrocoagulation field treatment. Graphical abstract: Image 1 Highlights: Iron-electrocoagulation (Fe-EC) is a promising contaminant removal technology. Previous studies show decreased Fe-EC performance over extended operation. We tracked iron dosed by Fe-EC over months with varied (electro)chemical parameters. Charge dosage rates ≥15 C/L/min and oxyanion-free solutions sustained high Fe doses. Decreased Fe dosing by Fe-EC was accompanied by thick electrode surface layers.